Decomposition responses to climate warming and sheep grazing in the high and sub-Arctic - Katrín Björnsdóttir 1991- (2018)
Tundra ecosystems are undergoing rapid environmental changes as the temperature rises at a rate unprecedented in modern human history. Permafrost soils in high latitude ecosystems contain enormous amounts of organic C and therefore play a crucial role in the global carbon cycle. If temperature changes follow current predictions, these carbon pools could potentially shift from a sink to a source of C by the end of this century due to accelerated decomposition rates. While many studies focus on the impacts of climate warming on tundra ecosystems, not as many include the impacts that herbivores can have on the ecosystem’s responses. Since herbivores can counteract some responses of tundra ecosystems to climate warming, investigation on plant–herbivore interactions is essential for understanding the responses of these ecosystems to a changing world. The main aim of this study was therefore twofold; (1) to examine how climate warming affects decomposition rates within tundra habitats in contrasting bioclimatic sub–zones in the Arctic, and (2) to examine how sheep grazing affects decomposition rates in Icelandic soils. Two different studies were carried out to test our hypotheses. The first study focused on the effects of climate warming on decomposition rates where open–top chambers (OTCs) were used to enhance temperature in five different habitats in sub–Arctic Iceland and high Arctic Svalbard. The second study focused on the effects of sheep grazing on decomposition rates where fences were used to exclude sheep grazing in two contrasting sites, within and outside the volcanically active zone in northern Iceland. In both studies protocols from the Tea Bag Index were used in order to estimate decomposition rates. Two types of commercially available tea were used to represent variable plant litter quality. In total 1,468 tea bags were buried into the ground and decomposition rates were estimated as four different decomposition variables (mass loss of green tea, mass loss of rooibos tea, stabilisation factor S and ...